Bioactive compounds derived from food matrices with therapeutic potential for Sars-Cov-2 infection: A review of in silico Studies (Research, Society and Development, 2021)
The study aimed to review the literature on available scientific evidence on the therapeutic potential that some bioactive compounds can exert on Sars-Cov-2 infection, based on tests performed with molecular docking techniques. The integrative review was carried out based on searches in electronic databases about publications of original articles written in English and Portuguese, between the years 2019 to 2021. The searches were carried out in the following databases: Science Direct (Elsevier Virtual Library), Scielo (Scientific Electronic Library Online), Pubmed/Medline (Medical Literature Analysis and Retrievel System Online) and VHL (Virtual Health Library), using as descriptors in health according to the DeCS/MeSH platform the words: Derived bioactive compounds of food, replication, SARS-CoV-2, in silico, in English and Portuguese, using the term ''and'' as a Boolean operator. After the search and selection process using the criteria mentioned in the methodology, 6 articles were selected. Natural products derived from food matrices could be a valuable source of new bioactive compounds to fight the COVID-19 pandemic. According to the results reported in this review, several natural compounds, including polyphenols and flavonoids, have shown the ability to prevent SARS-CoV-2 replication by inhibiting the main virus proteases, thus mitigating the clinical consequences of the infection, according to the in silico technique used.